Квадраты 2-ух выражений одинаковы, когда эти выражения одинаковы либо обратны:
(х^2 + 5)^2 = (5х - 1)^2;
- х^2 + 5 = -(5х - 1);
- х^2 + 5 = 5х - 1.
1. х^2 + 5 = -(5х - 1);
х^2 + 5 = -5х + 1;
х^2 + 5x + 4 = 0;
D = 5^2 - 4 * 4 = 25 - 16 = 9;
x = (-b D) / (2a);
x = (-5 9) / 2 = (-5 3) / 2;
x1 = (-5 - 3) / 2 = -8 / 2 = -4;
x2 = (-5 + 3) / 2 = -2 / 2 = -1.
2. х^2 + 5 = 5х - 1;
х^2 - 5x + 6 = 0;
D = 5^2 - 4 * 6 = 25 - 24 = 1;
x = (-b D) / (2a);
x = (5 1) / 2 = (5 1) / 2;
x3 = (5 - 1) / 2 = 4 / 2 = 2;
x4 = (5 + 1) / 2 = 6 / 2 = 3.
Ответ: -4; -1; 2; 3.
-
Вопросы ответы
Статьи
Информатика
Статьи
Математика.
Разные вопросы.
Разные вопросы.
Математика.
Разные вопросы.
Математика.
Физика.
Геометрия.
Разные вопросы.
Обществознание.